Priests and their Wigs in Eighteenth-Century Rome - Pattenden, Miles (Church history, 2024)
The wig was the quintessential accessory of eighteenth-century European culture, but the wearing of wigs by clerics became a subject of heated controversy across Catholic societies. Critics of clerical wig-wearing pointed to its inherent vanity, to Paul's proscription against men covering their heads in Church in 1 Corinthians 11, and to its apparent denial of the tonsure's importance as the visible outward sign of clerical status. However, defenders pointed to arguments about the need to cover up imperfections in the priest's body and avoid scandal. Various bishops moved to restrict the use of wigs amongst their diocesan clergy. However, no bishop was more active in legislating than the bishops of Rome themselves. Popes from Clement IX (r. 1667-69) to Pius VI (r. 1775-99) all issued instructions about clerical wig-wearing and their legislation betrays shifting attitudes and approaches. The most zealous rules from the 1720s gradually gave way to more pragmatic ones which attest to the persistent desire of Roman clerics to engage in male status competition and to the growing difficulty that the Church's leadership had in persuading them of the intrinsic superiority of their clerical status.